Republic of Sierra Leone : Assessment of National Public Procurement System Based on OECD/DAC Benchmarking Tool - World Bank (Washington, DC, 2012)
Sierra Leone is a post conflict country with a population of 6 million in an area of 71,740 square kilometers. Since the end of hostilities in 2002, the United Nations Development Program (UNDP), the African Development Bank (AfDB), the Department for International Development UK (DFID), the European Union (EU), and the World Bank (WB) have played significant roles in supporting the Government of Sierra Leone (GoSL) to rebuild the country for a brighter future. With the demobilization process complete and significant progress in terms of reconstruction, rehabilitation, humanitarian relief and the reestablishment of public service delivery, the GoSL has been focusing reforming and strengthening its governance systems. This report takes stock of the progress for reforms in the procurement system since 2004 and sets out the next steps to ensure continued progress towards establishing a modern and efficient and accountable public procurement system. This CPAR is divided into various sections which cover country context, PFM and procurement reform history, government-donor collaboration, and relation to the Country Assistance Strategy (CAS), the methodology used for this assessment, and the major findings and recommendations. The annexes present the detailed assessment report (using the Organization for Economic Cooperation and Development (OECD) and DAC BLI (baseline indicator tool), the detailed recommended action plan, National Competitive Bidding (NCB) exceptions from to conform to the bank procurement guidelines, and other relevant documentation.